Cytokines and Chemokines in Breastmilk of SARS-CoV-2 Infected or COVID-19 Vaccinated Mothers - Felicia Trofin; Olivia Simona Dorneanu; Daniela Constantinescu; Eduard Vasile Nastase; Cătălina Luncă; Luminița Smaranda Iancu; Ioana-Maria Andrioaie; Alexandru Duhaniuc; Corina Maria Cianga; Mariana Pavel-Tanasa; Dana-Teodora Anton-Păduraru; Petru Cianga (Vaccines, 2022)
Introduction: The COVID-19 disease and anti-SARS-CoV-2 vaccination were accompanied by alterations in several inflammatory markers. The aim of our research was to check to what extent such cytokines are transferred to infants via the breastmilk of SARS-CoV-2-infected or vaccinated mothers. Thus, we wanted to check if breastfeeding is safe during SARS-CoV-2 infection or after COVID-19 mRNA-vaccination. Material and method: The Luminex Multiplexing Assay was used for quantifying 10 cytokine in the human breastmilk of SARS-CoV-2-infected or COVID-19-vaccinated mothers, compared with anti-SARS-CoV-2 IgG naïve mothers. Two milk samples were collected at 30 and 60 days either after the booster dose or afterthe onset of symptoms. A single milk sample was collected from the mothers within the control group. Results: The cytokine concentrations were mostly found within the reference intervals for all mothers. The status of the vaccinated/infected mother, the age of the breastfed child, the parity of the mother and the maternal age were variation factors of the above-mentioned cytokine concentrations. The type of birth and the presence of IgG in the milk had no influence on these cytokine concentrations in milk. Furthermore, no statistically significant differences were recorded between the cytokine concentrations of the two milk samples. Conclusion: Our study provides data that support the safety of breastfeeding in the case of mild COVID-19 infection or after Pfizer or Moderna vaccinations.